Determinants of Credit Risk: Empirical Evidence from Chinese Commercial Banks - Chen, Mengjie (2019)
Abstract The rapid development of global economic and financial integration has brought pressure to the competition and credit risk management of commercial banks, especially in China. The size of credit risk will directly affect bank’s business status and future development. Therefore, this study mainly studies the determinants of the credit risk of commercial banks in China. By collecting the data of 47 Chinese commercial banks between 2014 and 2018, and then conducted a multiple regression model analysis of this panel data from two aspects, macroeconomic determinant, and microeconomic determinant. The main conclusion is that, on the one hand, when the economic develops reasonably well, the GDP growth rate with an upward trend could decline the credit risk faced by commercial banks. However, excessive inflation will raise the its credit risk. For microeconomic factors, leverage and management efficiency are both negatively correlated with credit risk. On the contrary, bank size, loan-to-deposit ratio, net interest margin, and loan loss provision are all positive influence on credit risk. In the end, this study provides some suggestions for commercial banks to adapt to the economic environment and prevent credit risks, such as adjusting loan investment objects, improving internal rating system, establishing database management system, creating a good credit culture and optimizing the business structure.